Conceptualizing and measuring instructional quality in mathematics education: A systematic literature review - Mu, Jin; Bayrak, Aslihan; Ufer, Stefan (Frontiers in Education, 2022)
Conceptualizing and measuring instructional quality is important to understand what can be understood as “good teaching” and develop approaches to improve instruction. There is a consensus in teaching effectiveness research that instructional quality should be considered multidimensional with at least three basic dimensions rather than a unitary construct: student support, cognitive activation, and classroom management. Many studies have used this or similar frameworks as a foundation for empirical research. The purpose of this paper is to investigate the relation between the conceptual indicators underlying the conceptual definitions of the quality dimensions in the literature, and the various operational indicators used to operationalize these factors in empirical studies. We examined (a) which conceptual indicators are used to conceptualize the basic dimensions theoretically, (b) to which extent the operational indicator in the literature cover these conceptual indicators, and (c) if which additional indicators are addressed by the measurement instruments, which are not part of the theoretical conceptualization. We conducted a systematic literature review on the conceptualization and operationalization of Instructional Quality in Primary and Secondary Mathematics Education based on PRISMA procedures. We describe the span of conceptual indicators connected to the three basic dimensions over all articles (a) and analyze to which extent the measurement instruments are in line with these conceptual indicators (b, c). For each measurement dimension, the identified quality dimensions identified are, taken together, largely representative of the conceptual indicators connected to the core factor, but also a number of critical misconceptions occurred. Our review provides a comprehensive overview of the three basic dimensions of instructional quality in mathematics based on theoretical conceptualizations and measurement instruments in the literature. Beyond this, we observed that the descriptions of a substantial amount of quality dimensions and their conceptualizations did not clearly specify if the intended measurement referred to the learning opportunities orchestrated by the teacher, or the utilization of these opportunities by students. It remains a challenge to differentiate measures of instructional quality (as orchestrated by the teacher) from (perceived) teacher competencies/knowledge, and students’ reactions to the instruction. Recommendations are made for measurement practice, as well as directions for future research.